Long-term changes in body build of male and female judo competitors - Pietraszewska, J.; Burdukiewicz, A.; Stachon, A.; Andrzejewska, J.; Chromik, K. (Central European Journal of Sport Sciences and Medicine, 2018)
The aim of the study was to determine if changes in the body build of judo athletes over a time span of 20 years are in line with trends described in the literature. Anthropometry of 60 male and 46 female judokas was performed. Data was collected from two cohorts: the first involved 30 males and 23 females measured in 1994-1995 and the second 30 males and 23 females in 2013. Anthropometric profiles included measurements of skinfolds, height, weight, and body and segment lengths, breadths, and girths. Although relatively identical heights and weights were found between the cohorts, significant differences were detected for body proportion measures. Males in 1994-1995 showed a significantly longer trunk, wider shoulders and hips, and more subcutaneous adipose tissue than the 2013 cohort. Females in 1994-1995 showed a shorter trunk, larger diameters of the trunk in relation to body height, and significantly lower skinfold thicknesses than the 2013 cohort. The direction of changes in the physical characteristics of judokas should be taken into consideration by coaches during training. Combat techniques should be adapted to the morphological traits of the athletes to achieve success and minimize the risk of overloading or injury.